Evaluation of the main parameters of the compartmental model of the epidemic development based on the example of the spread of the COVID-19 pandemic in Chernivtsi region - Nahirniak , V.M. (Medicni Perspektivi, 2023)
The paper considers the application of the theoretical model of epidemiological development of COVID-19 disease among the regional population based on the statistical data in Chernivtsi region of Ukraine for the period from March 2020 to June 2021. Using these data, a mathematical assessment of the values of the main parameters of the compartmental model (SIR) β and γ was performed and the analysis of the relationship between the values of β and γ and antiepidemiological measures was carried out for the region. Determining the parameters β and γ based on available statistics allows us to predict the duration of precautionary measures such as quarantine, lockdown, border closure and predict the effectiveness of their implementation as well. The analysis of statistical data showed the moderate effectiveness of quarantine and lockdown in changing the daily rates of infected and recovered people, while the dynamics of the epidemic development during these periods changed from negative to positive. The introduction of vaccination has shown the significant reduction in the daily rate of infected people and the substantial increase in the daily rate of the recovered people.